Organizational Impact on Commitment Performance: Research on Police Officer at Polsek Kotagede Yogyakarta - Endah Sri Wahyuningsih (Psychological Research and Intervention, 2020)
This research is aimed at examining the significance of the effect of organizational commitment on individual performance, especially national police members. Polri's performance is determined by several factors, situations and relationships between corps. Bad corps' performance will impact the performance of the other corps. For intensifying performances, many things can be done. One of them is organizational commitment. The Research subjects were all of Kotagede Police Members Yogyakarta to 59 people. Data collection method that the researcher used was spread the commitment scale which contains statements about organizational commitment variables, whereas for performance variables researchers used performance data of the National Police's members of the Polsek Kotagede Polresta of Yogyakarta. Data were analyzed by using simple regression analysis with the help of the SPPS 21 statistical program. The result shows a significant influence of organizational commitment on the performance of Polri members by 12.9%, while the remaining 79.1% were influenced by other variables not examined.